Lumen-apposing metal stents versus biliary fully-covered metal stents for EUS-guided drainage of pancreatic fluid collections: a case control study - Garcia Garcia de Paredes, Ana; Gonzalez Martin, Juan Angel; Foruny Olcina, Jose Ramon; Juzgado Lucas, Diego; Gonzalez Panizo, Fernando; Lopez Duran, Sergio; Martinez Sanchez, Alba; Sanjuanbenito, Alfonso; Caminoa, Alejandra; Albillos, Agustin; Vazquez-Sequeiros, Enrique (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound (EUS)-guided drainage has become first-line treatment for pancreatic fluid collections (PFC). The aim of this study was to compare the effectiveness and safety of biliary fully-covered self-expandable metal stents (BFCSEMS) and lumen-apposing metal stents with electrocautery (EC-LAMS).Patients and methods From April 2008 to March 2017, consecutive patients with symptomatic PFC drained under EUS-guidance with metal stents were included. Patients drained with EC-LAMS were considered the study group and those drained with BFCSEMS the control group. Two primary endpoints were evaluated: effectiveness (defined as reduction of ≥ 50 % of PFC size in cross-sectional imaging and improvement of symptoms 6 months after the transmural drainage) and safety.Results Thirty patients were drained with EC-LAMS and 60 patients with BFCSEMS. Patients and PFC baseline characteristics in both groups were similar. Use of a coaxial double pigtail plastic stent and a nasocystic lavage catheter was significantly less frequent in patients drained with EC-LAMS (33 % vs. 100 %, and 13 % vs. 58 %, respectively; P < 0.0001). Technical success was 100 % in both groups. Procedure time was < 30 minutes in all patients drained with EC-LAMS and over 30 minutes in all patients drained with BFCSEMS (P = 0.0001). Clinical success was higher with a tendency to significance in patients drained with EC-LAMS (96 % vs. 82 %, P = 0.055) and the adverse event rate was lower (4 % vs. 18 %, P = 0.04). No case of procedure-related mortality was recorded.Conclusions EC-LAMS and BFCSEMS are both effective for EUS-guided drainage of PFC. However, EC-LAMS requires less time to be performed and appears to be safer.